2020
DOI: 10.3390/jcm9103078
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Conditions in Chronic Obstructive Pulmonary Disease: Potential Therapeutic Targets for Unmet Needs

Abstract: The management of chronic obstructive pulmonary disease (COPD) has improved significantly due to advances in therapeutic agents, but it has also become apparent that there are issues that remain difficult to solve with the current treatment algorithm. COPD patients face a number of unmet needs concerning symptoms, exacerbations, and physical inactivity. There are various risk factors and triggers for these unmet needs, which can be roughly divided into two categories. One is the usual clinical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 176 publications
(222 reference statements)
0
29
0
Order By: Relevance
“…The frailty group in the patients with PROMs-D score 1-2 had a higher CCI score than the non-frailty group. Since comorbid conditions in COPD are closely related to respiratory symptoms, exacerbations, and physical inactivity, it is important to identify therapeutic targets for these unmet medical needs [25]. Several studies have reported that comorbidities in COPD are associated with an increased risk of frailty [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The frailty group in the patients with PROMs-D score 1-2 had a higher CCI score than the non-frailty group. Since comorbid conditions in COPD are closely related to respiratory symptoms, exacerbations, and physical inactivity, it is important to identify therapeutic targets for these unmet medical needs [25]. Several studies have reported that comorbidities in COPD are associated with an increased risk of frailty [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The Kihon Checklist (KCL) is a self-administered questionnaire developed by the Japanese Ministry of Health, Labor, and Welfare to predict functional decline in community-dwelling elderly [29]. The KCL consists of 25 "yes/no" questions and divided into seven domains: 1 7depressive mood (questions [21][22][23][24][25]. The total KCL score, which is a sum of 25 answers, ranges from 0 (no frailty) to 25 (severe frailty).…”
Section: Definition Of Frailty Using the Kihon Checklistmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic obstructive pulmonary disease (COPD) is a complex and persistent lung disease, kills more than 3 million people worldwide every year (1). Despite progress in comprehensive therapies and prevention of acute exacerbations over past decades, therapeutic advances in ameliorate disease progression or reduce mortality remains few (2,3). Therefore, it is needed to have a better understanding of the complex disease mechanisms and explore better biomarkers to assess and monitor disease risk and prognosis.…”
Section: Introductionmentioning
confidence: 99%